Determination of the Decision to Use Maybank Securities SOTS on UIN Sumatera Utara Students with the UTAUT Approach - Nadzira Putri Andani; Muhammad Lathief Ilhamy Nst; Muhammad Ikhsan Harahap (BASKARA : Journal of Business and Entrepreneurship, 2025)
This study aims to analyse the factors influencing the decision of UIN Sumatera Utara students to use the Sharia Online Trading System (SOTS) of Maybank Securities using the Unified Theory of Acceptance and Use of Technology (UTAUT) approach. This model includes variables such as performance expectancy, effort expectancy, social influence, facilitating conditions, and an additional variable of Islamic financial literacy as a factor that may influence usage decisions. The research employs a quantitative approach with an associative research design. Primary data was collected through surveys distributed to UIN Sumatera Utara students who are clients of Maybank Securities. The research sample was determined using the Slovin formula, resulting in 89 respondents. Data analysis was conducted using validity and reliability tests, classical assumption tests, and multiple linear regression analysis with the assistance of SPSS software. The results indicate that performance expectancy, social influence, and Islamic financial literacy significantly affect the decision to use SOTS Maybank Securities. Conversely, effort expectancy and facilitating conditions do not have a significant influence. Simultaneously, the variables in the UTAUT model contribute 70.1% to the decision to use SOTS, while other factors beyond this research model influence the remaining 29.9%. These findings suggest that improving Islamic financial literacy and encouragement from the social environment can enhance students' interest in using digital-based Sharia investment services